THINKING AND ITS DEVELOPMENTAL CHARACTERISTICS DURING THE PRESCHOOL AGE PERIOD - Toshboltayeva Nodira Ibrohimjonovna (Bright Mind Publishing, 2025)
This article psychologically analyzes the influence of pronouncements on the thinking process, the continuous relationship between consciousness and unconsciousness, and the stages and levels of thinking as a process. Also, the conditional stages of the thinking process, arising under the influence of pronouncements, are psychologically explained.
Keywords: Consciousness and unconsciousness, consciousness and unconsciousness, empathy, reflexivity, psychological structure, cognitive style, modern imagination, intellectual activity.